A systematic review of capnography for sedation. (21st January 2016) - Conway, A.; Douglas, C.; Sutherland, J. R.
Summary: We included six trials with 2524 participants. Capnography reduced hypoxaemic episodes, relative risk (95% CI) 0.71 (0.56–0.91), p = 0.02, but the quality of evidence was poor due to high risks of performance bias and detection bias and substantial statistical heterogeneity. The reduction in hypoxaemic episodes was statistically homogeneous in the subgroup of three trials of 1823 adults sedated for colonoscopy, relative risk (95% CI) 0.59 (0.48–0.73), p < 0.001, although the risks of performance and detection biases were high. There was no evidence that capnography affected other outcomes, including assisted ventilation, relative risk (95% CI) 0.58 (0.26–1.27), p = 0.17. Abstract : ☛ CPD available athttp://www.learnataagbi.org